Philanthropy in the perspective of Islamic economics and its practices among Indonesian Muslim entrepreneurs: a divine insurance and investment - -, Susy Yunia R. Sanie (2023)
This article tries to explain the rationality of Muslim consumers, aka homo Islamicus, in carrying out philanthropic actions. It is explained from an Islamic Economics perspective why people are willing to sacrifice their economic resources, in the form of: money, time and energy for the benefit of others, such as donating, volunteering or participating in mutual cooperation. This study apply 2 step of methodology: first, qualitative method using a literature study, and second, quantitative method thru a survey. In the first step, both approaches of the religious economics and the economics of religion are combined use to achieve the objectives of this article. Economic concepts, formulas, curves, graphs and consumer rational choice theory are applied in describing how believers carry out God's command written in the holy book to give alms. On the second step, a survey using face-to-face interviews of 300 middle-up class Indonesian muslim entrepreneurs who were rich enough to be zakat payers (muzakki) was conducted to prove the existence of philanthropic practices in the form of alms of gratituted (sadaqah syukur) and alms of desire (sadaqah hajat). The selection of respondents was carried out using the multiple quasirandom sampling method. Data was analyzed using descriptive statistics by showing gender differences. In the perspective of Islamic Economics, alms is not ordinary consumption. People do it to gain safety or protection from anything they worries, and also to ensure that their hopes and desires will come true. This motives are derivated from the Al Qur’an verses and Hadith. Therefore, donations are more suitable to be categorized as insurance as well as divine investments, because God is the guarantor. Survey results showed that most of the respondents (88.4%) respondents who issue "alms of gratitude or sadaqah syukur" which is to increase alms if they get additional income in the form of additional fortune/"rezeki nomplok", big profits and success, etc., although with different intensities (rarely, sometimes, often and always). It is the proof of positive relationship between income and alms. On the other hand, the majority (85.6%) of respondents also admitted they did special alms if they need Allah to fulfill they wish or hope, especially to ward off evil that they worry about, which called "alms of wish or sadaqah hajat". Further research is recommended to quantitatively analyze the factors that influence people's giving of alms. Among the influencing factors, such as personal or household income, household dependency ratio, religious observance and level of religiousity should be variables considered. Socialization of the meaning concepts of "alms of gratitude or sadaqah syukur" and "alms of wish or sadaqah hajat" can be a strategy in an effort to increase almsgiving behavior for the government and Islamic philanthropic institutions such as BMT (Baitul Mal wal Tamwil) or LAZIS (Zakat, Infaq and Sadaqah Collecting Institute). This study contributes the defenition concept of the believer (homo religious) which reflects the image of a true human being based on his nature, as a correction to the concept of the economic man (homo economicus), so that it can be applied to every man from all religions, even the atheists. Based on an understanding of the true human, the concept of utility regarding human needs and satisfaction from the goods/services they consume is expanded. The proposed concept of “Maslahah” is total utility from all benefits can be gained by real human from his/her decision to get a product or service by spending their economically resouces, namely: physical/material benefit, psychological benefit, social benefit, spiritual benefit, and religious benefit. So it can explain the rationality of altruistic behavior, including giving alms and other philanthropic acts, because by giving to others, one still gaining self-benefit both in this mortal world life and eternal life hereafter. The contribution of new ideas regarding the concept of "alms of gratitude or sadaqah syukur" and "alms of wish or sadaqah hajat" is an effort to support the initiative to "grounding the Al-Qur'an verses and Hadith on earth" so that Allah's rules are easier to understand and implement in people's daily lives.